The Lived Experiences of Occupational Therapists in Transitioning to Leadership Roles - Shawn Sasha Shams; Ravneet Batth; Andrea Duncan (Scholarworks @ WMU, 2019)
Background: Several studies on leadership in occupational therapy have discussed the key qualities of leadership and its importance, even though little is known about the transition process into leadership roles. This research examined the lived experiences of occupational therapists who have transitioned from a clinical to a leadership role and identified the supports and challenges that were found to be important. Methods: Semi-structured interviews were used to gain insight into the transition process of five occupational therapy professional practice leaders. NVivo software was used to organize and analyze the qualitative data. Results: Three common themes were identified as "supports" for participants in their transitions: (a) intrinsic motivation, (b) support systems, and (c) an occupational therapy perspective. Three common themes were identified as "challenges": (a) changes in interpersonal relationships, (b) systemic factors, and (c) steep learning curve. Conclusion: The findings of this study highlight the importance of leadership-specific education, family support, extensive clinical experience, and implementation of leadership-specific resources in the occupational therapy curriculum.